The Implementation Model of Premium Tariff to Accelerate the Use of Photovoltaic (PV) Rooftop in Jakarta - Prasetya, Muhammad Rezansyah Tangguh; Dalimi, Rinaldy (Nusantara Science and Technology Proceedings, 2021)
The renewable energy mix achievement in 2019 was 10,2 GW still under the national target which is 13,9 GW, where PV Rooftop only contributed for 0,19% (19,57 MW). In order to accelerate the use of PV Rooftop, a Premium Tariff of PV Rooftop need to be implemented by PT. PLN. To set the Premium Tariff research needed to be conducted to obtain the total of Premium Tariff and its implementation. In the implementation, customers will have the PV Rooftop with installment payments, however the excess energy that produced by PV Rooftop stated in Kilowatt Hour (Kwh) does not count as a reduction in the electricity bills until the end of the contract duration. In this research used quantitative and qualitative methods. Quantitative method, a calculation conducted to obtain the Premium Tariff that can be offered to customers. Whereas the qualitative is conducted a survey to see the customer interest on PV Rooftop and the selection of the Premium Tariff offer. In the research results showed 77% customers of R2 (PLN Rate) in Jakarta are interested to use PV Rooftop however constrained by high initial investment. Therefore, installment payment scheme is offered with contract duration of 13 years for the capacity power 3.500 VA, 8 years for 5.500 VA with the Rates ranging from IDR 1.444/Kwh to IDR 3.232/Kwh. With the assumption that 77% customers of R2 Rate in Jakarta used Premium Tariff, it can increase the usage capacity of PV Rooftop by 220 - 800 MW.